Stem Cell Transplantation in 6 Children with Parvovirus B19- Induced Severe Aplastic Anaemia or Myelodysplastic Syndrome - Urban, C.; Lackner, H.; Müller, E.; Benesch, M.; Strenger, V.; Sovinz, P.; Schwinger, W. (Klinische Pädiatrie, 2011)
Parvovirus B19 (PVB19) induced severe aplastic anaemia (SAA) or myelodysplastic syndrome (MDS) is rare, and haematopoietic stem cell transplantation (HSCT) in this condition has not been reported so far. 6 children with SAA (n=4) or MDS (n=2) caused by acute PVB19 infection underwent HSCT under the protection of intravenous immunoglobulines. The 4 children with SAA received matched HLA bone marrow from a sibling (n=3) or peripheral unrelated blood stem cells (n=1). 1 patient had delayed erythrocyte engraftment, whereas 3 patients had an uneventful transplantation course. HSCT in one of the 2 children with MDS was complicated by poor graft function, the other patient engrafted without complications. In conclusion, HSCT in children with PVB19 induced SAA or MDS is feasible, even though some patients may develop delayed engraftment or prolonged poor graft function.
Keywords: pediatrics; haematology; stem cell transplantation; parvovirus B19